Identifying Prognostic Criteria for Survival after Resuscitation Assisted by Extracorporeal Membrane Oxygenation. (23rd February 2016) - Brunner, Alexandrine; Dubois, Natacha; Rimensberger, Peter C.; Karam, Oliver
Abstract : To improve survival rates during CPR, some patients are put on extracorporeal membrane oxygenation (ECMO). Among children who have undergone ECMO cardiopulmonary resuscitation (ECPR), the overall rate of survival to discharge is close to 40%. However, despite its wide acceptance and use, the appropriate indications and organizational requirements for ECPR have yet to be defined. Our objective was to assess the clinical outcomes of children after ECPR and to determine pre-ECPR prognostic factors for survival to guide its indication. Among the 19 patients who underwent ECPR between 2008 and 2014 in our center, 16 patients (84%, 95% confidence interval: 62–95%) died during their hospital stay, including nine (47%) who were on ECMO and seven (37%) after successful weaning from ECMO. All three survivors had normal cognitive status, but one child suffered from spastic quadriplegia. Survivors tended to have lower lactate, higher bicarbonate, and higher pH levels before ECMO initiation, as well as shorter length of resuscitation. In conclusion, in our center, ECPR has a poorer outcome than expected. Therefore, it might be important to identify, a priori, patients who might benefit from this treatment.